From market fixing to market-creating: a new framework for innovation policy. Issue 2 (17th February 2016) - Mazzucato, Mariana
Abstract: Many countries are pursuing innovation-led "smart" growth, which requires long-run strategic investments and public policies that aim to create and shape markets, rather than just "fixing" markets or systems. Market creation has characterized the kind of mission-oriented investments that led to putting a man on the moon and are currently galvanizing green innovation. Mission-oriented innovation has required public agencies to not only "de-risk" the private sector, but also to lead the direct creation of new technological opportunities and market landscapes. This paper considers four key issues that arise from a market-creating framework for policy: (1) decision-making on the direction of change; (2) the nature of (public and private) organizations that can welcome the underlying uncertainty and discovery process; (3) the evaluation of mission-oriented and market-creation policies; and (4) the ways in which both risks and rewards can be shared so that smart growth can also result in inclusive growth.